Predictive biomarkers of mortality in patients with severe COVID-19 hospitalized in intensive care unit - dos Santos Medeiros, Sandrelli Meridiana de Fátima Ramos; Sousa Lino, Bruna Maria Nepomuceno; Perez, Vinícius Pietta; Sousa, Eduardo Sérgio Soares; Campana, Eloiza Helena; Miyajima, Fábio; Carvalho-Silva, Wlisses Henrique Veloso; Dejani, Naiara Naiana; de Sousa Fernandes, Matheus Santos; Yagin, Fatma Hilal; Al-Hashem, Fahaid; Elkholi, Safaa M.; et al. (Frontiers in Immunology, 2024)
Objectives: This study was performed to identify predictive markers of worse outcomes in patients with severe COVID-19 in an intensive care unit. Methods: Sixty patients with severe COVID-19, hospitalized in the Intensive Care Unit (ICU) between March and July 2021, were stratified into two groups according to the outcome survivors and non-survivors. After admission to the ICU, blood samples were collected directly for biomarker analysis. Routine hematological and biochemical biomarkers, as well as serum levels of cytokines, chemokines, and immunoglobulins, were investigated. Results: Lymphopenia, neutrophilia, and thrombocytopenia were more pronounced in non-surviving patients, while the levels of CRP, AST, creatinine, ferritin, AST, troponin I, urea, magnesium, and potassium were higher in the non-surviving group than the survival group. In addition, serum levels of IL-10, CCL2, CXCL9, and CXCL10 were significantly increased in patients who did not survive. These changes in the biomarkers evaluated were associated with increased mortality in patients with severe COVID-19.